Collaborative Governance in Poverty Reduction in Bandung City - Riana Permani (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
The main strategy of poverty alleviation in Bandung is directed to reduce the poverty rate. But the countermeasures that have been done by the relevant parties have not reached the target set. BPS data in 2019 showed the number of poor people reached 84,670 or 3.38% of the total population. In the last five years, the poverty rate has never reached 1% in accordance with the RPJMD target. On the other hand, all parties agree on the importance of building a system of partnership, coordination, and collaboration between local governments, communities, and non-governmental organizations in collaborative governance. The establishment of the Coordination Team for The Acceleration of Poverty Alleviation (TKPK) Kota Bandung became an important forum in achieving the target of reducing poverty rates. This research aims to find out how the implementation of collaborative governance principles at TKPK Kota Bandung. This study uses a qualitative approach with a descriptive analysis method to find out the existing condition of ongoing collaboration. The data source is obtained from in-depth interviews, field observations as well as secondary data. The results showed that the principles of collaborative governance by TKPK Kota Bandung have not been optimal. The existence of a special meeting forum is more often very important to build a common understanding of the roles and responsibilities of each stakeholder. Optimization of facilitative leadership and institutional design is also indispensable to provide encouragement to the collaboration process that tends to be slow to show temporary results.